Game-Based Learning: A Solution for Improving the Quality of Learning Processes and Outcomes in Elementary Schools - Aulia Yolanda, Sylvi; Susanti, Refnis; Indah Cahyani, Rahmi; Hadi, Ariseftian; Eka Putri, Nada; Mutathahirin, Mutathahirin (International Journal of Islamic Teaching and Learning, 2025)
Kahoot, as one of the technology-based media, allows learners to participate in real-time interactive quizzes, not only making the learning atmosphere more fun but also encouraging them to be more active in understanding the material. This study aims to evaluate the effectiveness of implementing the Game-Based Learning model assisted by Kahoot interactive media in improving the learning achievement of Natural Science and Social Science of fourth grade elementary school students. This study was conducted using participant-type classroom action research method, which was implemented in one of the elementary schools in West Sumatra, Indonesia. The respondents consisted of thirteen students, ten boys and three girls. This research was conducted in the form of a cycle, which began with planning, action, observation, and reflection. The researcher became a participant in the research and observed the implementation of actions in learning assisted by a senior teacher to observe with observation instruments. Data analysis was carried out with SPSS 25 to process data on student learning outcomes, while observation data was analyzed thematically. The results showed that game-based learning using Kahoot media is considered effective in providing energy material in Natural Science and Social Science learning in elementary schools. In the first cycle, the average success achieved by students increased significantly to 81.3%, and this success further increased in the second cycle, with the average achievement reaching 91.3%. This research implies that Kahoot media in science and social studies learning can be an option to create interactive and fun learning, especially for elementary school students.